Market Transparency, Adverse Selection, and Moral Hazard - Klein, Tobias J.; Lambertz, Christian; Stahl, Konrad O. (Journal of Political Economy, 2016)
We study how an improvement in market transparency affects seller exit and continuing sellers’ behavior in a market setting that involves informational asymmetries. The improvement was achieved by reducing strategic bias in buyer ratings. It led to a significant increase in buyer satisfaction with seller performance, but not to an increase in seller exit. When sellers had the choice between exiting—a reduction in adverse selection—and staying but improving behavior—a reduction in moral hazard—they preferred the latter. Increasing market transparency led to better market outcomes.